Polythiophene Based Composite with Enhanced Dielectric Performance with Basalt - Karabul, Yasar; Kilic, Mehmet; Ozdemir, Zeynep Guven; Erdonmez, Seda; Icelli, Orhan (SPRINGER, 2018)
In this work, Polythiophene/Basalt (PT/Basalt) composites with 4 and 8% (wt/wt) Basalt contents have been prepared by chemical method. The chemical composition of the basalt, which is a type of volcanic rock, has been determined by XRF technique. The surface morphology and chemical properties of the composites have also been analyzed by SEM and FTIR measurements. The dielectric spectra of pure PT and basalt doped PT composites have been investigated by impedance spectroscopy analysis performed within 1 Hz-40 MHz frequency region for 293-373 K temperature interval. The frequency dependences of the real and imaginary components of complex dielectric function revealed that the system can be considered as layered structure which consists of well conducting grains surrounded by poorly conducting grain boundaries and defined by Koop's bilayer theory. Moreover, basalt doping increases values which represents the charge storage ability of the dielectric material. Especially, the highest charge storage ability at room temperature has been determined for 8% basalt doped PT composite. The ac conductivity mechanism for the samples has also been determined as Correlated Barrier Hoping mechanism. Complex electrical modulus analysis also indicated non-Debye type of relaxation and temperature dependent hoping mechanism for the samples. Activation energy values determined from dc conductivity versus the inverse of the temperature curves of the samples have also revealed that as an inorganic and very cheap natural basalt doping makes the polythiophene better insulating material.
Keywords: Polythiophene; Volcanic rock; Basalt; Dielectric material; Impedance spectroscopy; ACETYLACETONATE COMPOSITES; AC CONDUCTIVITY; OXIDE; NANOCOMPOSITES; RELAXATION; IMPEDANCE; DIOXIDE; FILMS; Polymer Science